Main Ethiopian Rift landslides formed in contrasting geological settings and climatic conditions - K. Martínek; K. Martínek; K. Verner; K. Verner; T. Hroch; L. A. Megerssa; L. A. Megerssa; V. Kopačková; D. Buriánek; A. Muluneh; R. Kalinová; M. Yakob; et al. (Natural Hazards and Earth System Sciences, 2021)
The Main Ethiopian Rift (MER), where active continental rifting creates specific conditions for landslide formation, provides a prospective area to study the influence of tectonics, lithology, geomorphology, and climate on landslide formation. New structural and morphotectonic data from central Main Ethiopian Rift (CMER) and southern Main Ethiopian Rift (SMER) support a model of progressive change in the regional extension from NW–SE to the recent E(ENE)–W(WSW) direction, driven by the African and Somali plates moving apart with the presumed contribution of the NNE(NE)–SSW(SW) extension controlled by the Arabian Plate. The formation and polyphase reactivation of faults in the changing regional stress field significantly increase the rocks' tectonic anisotropy, slope, and the risk of slope instabilities forming.